Water-energy nexus-based scenario analysis for sustainable development of Mumbai. (December 2020) - De Stercke, Simon; Chaturvedi, Vaibhav; Buytaert, Wouter; Mijic, Ana
Abstract: The urban water-energy nexus sits at the intersection of the global phenomena of water scarcity, energy transitions and urbanisation. Research found that end use dominates the water-energy nexus and that this component plays an important role in urban dynamics, but focussed on the Global North. We investigate the nexus of Mumbai and its long-term resource demand. Our tool is a novel system dynamics model representing the urban water-energy nexus and takes into account characteristics such as intermittent water supply and the presence of slums. We devised scenarios around the Sustainable Development Goals and the Swachh Bharat Mission. The model shows that both can be achieved while saving on future water system infrastructure investments compared to business-as-usual. We find that also in Mumbai end use dominates the nexus. Representing end-use interactions increases expected water demand. This work indicates that globally, sustainable development of infrastructure must consider the urban water-energy nexus. Highlights: A system dynamics model explores the water-energy nexus of Greater Mumbai out to 2050. Including the effects of energy use on water use increases expected water consumption. End use has the greatest share in the nexus, in line with Global North. Meeting the SDGs requires better housing but could save on water infrastructure.